2(2x-9)-2x=2(x-2)-7

Simple and best practice solution for 2(2x-9)-2x=2(x-2)-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2x-9)-2x=2(x-2)-7 equation:


Simplifying
2(2x + -9) + -2x = 2(x + -2) + -7

Reorder the terms:
2(-9 + 2x) + -2x = 2(x + -2) + -7
(-9 * 2 + 2x * 2) + -2x = 2(x + -2) + -7
(-18 + 4x) + -2x = 2(x + -2) + -7

Combine like terms: 4x + -2x = 2x
-18 + 2x = 2(x + -2) + -7

Reorder the terms:
-18 + 2x = 2(-2 + x) + -7
-18 + 2x = (-2 * 2 + x * 2) + -7
-18 + 2x = (-4 + 2x) + -7

Reorder the terms:
-18 + 2x = -4 + -7 + 2x

Combine like terms: -4 + -7 = -11
-18 + 2x = -11 + 2x

Add '-2x' to each side of the equation.
-18 + 2x + -2x = -11 + 2x + -2x

Combine like terms: 2x + -2x = 0
-18 + 0 = -11 + 2x + -2x
-18 = -11 + 2x + -2x

Combine like terms: 2x + -2x = 0
-18 = -11 + 0
-18 = -11

Solving
-18 = -11

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -57+17=-5x+13x | | -10(7+m)=-230 | | 34.5=(2)(3.14)(x) | | 1.1x+1.2x-5.4=-16 | | -7n=-98 | | p^2+p=x | | 59.7=(2)(3.14)(x) | | 8-6a=4(a-3) | | -1.333333+y+y=3 | | 3120=(26000)(0.03)(x) | | 0=12-5x+3y | | ax-r=12 | | 4(6p-8)=24p-23 | | 15r=60 | | 43z-1=4(13z-16) | | -10x+9x=-9+10 | | 1.43x(-19/37)= | | -4z-4z=3z+3+3z | | 30-10k=22-2k | | 7=12z+18-5 | | Y=yz+10 | | -8(-8x-6)=-6x-222 | | s+7(4)=16 | | 193=3+10p | | -3(-3+y)+3y=4 | | -5m=-85 | | -7(x+4)=0 | | 6n-2(3-n)=-13 | | 44+2c=7c-6 | | x/13=-7 | | 3x+3/3= | | 6(2m-1)-1(11m+6)=7 |

Equations solver categories